Impact of Investment Inflows on Regional Disparity in Indonesia - Firdaus, Muhammad (2006)
Some tactical policies related to regional development, whether they were intended or not, were implemented since in the early 1970s. Moreover some policies have been formulated in 1990s to reduce regional disparities. However, they are more in nonnative level than implementation. An increasing level of regional income inequality, which accompanied the rapid economic growth, shows the failure of some those policies. The large differences in economic indicators among provinces in Indonesia are no doubt due to the very significant inequality of investment inflows. The problem of economic disparity across Indonesia will still exist. This study aims to analyze the disparity of regional economy by testing the income convergence; to identify the relationship between regional income and investment inflows and to find the determinants of foreign investment inflows into provinces. The shortcomings of the cross-sectional approach have advocated the time-series estimation. However the time-series estimates may be subject to problems of identification and estimation induced by simultaneity bias or endogeneity of variables observed. Based on such disadvantages, both static and dynamic panel data methods are employed to satisfy the objectives of this study. This study shows that static and dynamic panel data approach give the different results of convergence examination. Consistent with the theory, the OLS and fixed-effects estimators provide the upper and lower bounds. The first-differences generalized method of moments (FD-GMM) provides invalid estimators which are lower than the coefficient from the fixed effects estimators due to the weak instruments problem. The system GMM (SYS-GMM) estimators are found to be unbiased, consistent and valid. They show that convergence process prevails among provinces in Indonesia for the period 1983 - 2003. However the speed of convergence is .29 percent, which is relatively very slow compared to other studies in developing countries. The model suggests that regional income and investment inflows show the positive and significant relationship. The SYS-GMM are also the most preferred model for finding the determinants of foreign investment inflows. The results of this study show that factors which are statistically significant to attract the foreign investors to come to a province are market size (regional GDP), level of economic development (agriculture's share), infrastructure (electric supply) and education level attainment.